The roles of BTG1 mRNA expression in cancers: A bioinformatics analysis - Zheng, Hua-chuan; Xue, Hang; Zhang, Cong-yu; Shi, Kai-hang; Zhang, Rui (Frontiers in Genetics, 2022)
BTG1 (B-cell translocation gene 1) may inhibit proliferation and cell cycle progression while also inducing differentiation, apoptosis, and anti-inflammatory activity. The goal of this study was to clarify the clinicopathological and prognostic significances of BTG1 mRNA expression and related signal pathways in cancers. Using the Oncomine, TCGA, Xiantao, UALCAN, and Kaplan-Meier plotter databases, we undertook a bioinformatics study of BTG1 mRNA expression in cancer. BTG1 expression was lower in gastric, lung, breast and ovarian cancer than normal tissue due to its promoter methylation, which was the opposite to BTG1 expression. BTG1 expression was positively correlated with dedifferentiation and histological grading of gastric cancer (p<0.05), with squamous cell carcinoma, young and male lung cancer patients (p<0.05), with infrequent lymph node metastasis, low TNM staging, young patient, white race, infiltrative lobular carcinoma, Her2 negativity, favorable molecular subtyping, and no postmenopause status (p<0.05), and with elder age, venous invasion, lymphatic invasion, and cliniopathological staging of ovarian cancer (p<0.05). BTG1 expression was negatively correlated with favorable prognosis of the gastric, lung or ovarian cancer patients, but the converse was true for breast cancer (p<0.05). KEGG analysis showed that the top signal pathways included cytokine-cytokine receptor interaction, cell adhesion molecules, chemokine, immune cell receptor and NF-κB signal pathways in gastric and breast cancer. The top hub genes mainly contained CD antigens in gastric cancer, FGF-FGFR in lung cancer, NADH: ubiquinone oxidoreductase in breast cancer, and ribosomal proteins in ovarian cancer. BTG1 expression might be employed as a potential marker to indicate carcinogenesis and subsequent progression, even prognosis.